ETIKA BERMUSIK DALAM ISLAM - Alihan Satra; Anugrah Putri Sakti; Siti Holijah; Rahma Alia El Zahra; Ahmad Farhan Pratama (Institut Agama Islam Hamzanwadi NW Lombok Timur, 2025)
This study discusses the issue of music ethics in Islam which is still a debate among Muslims and scholars. The aim is to understand the diverse views on music, both from the perspective of ethics, Islamic law, history, and the opinions of contemporary scholars. This study uses a qualitative method with a library study approach, namely by reviewing various literature and religious sources from various schools of thought and the opinions of scholars to obtain a holistic understanding. The results of the study show that music in Islam cannot be decided absolutely halal or haram, but rather depends on the context, content, intention, and social and spiritual impacts of the music. Some scholars forbid music because it is considered to neglect religious obligations, while others allow it under certain conditions, such as wedding celebrations or preaching. Thus, it can be concluded that music must be understood proportionally and contextually within the framework of Islamic values, and music ethics are important so that this art remains in line with religious principles.